Differential patterns of persistent opioid use in patients with cancer and non-cancer pain - Abdullah Sani, Asween Rowena; Zin, Che Suraya; Mohamad Noor, Zaswiza; Mohamed, Abdul Hadi; Nissen, Lisa M. (Elsevier, 2016)
OBJECTIVES: This study aims to evaluate different patterns of persistent opioid use in patients with cancer and non-cancer pain.